2022
DOI: 10.1088/2057-1976/ac536b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an advanced cone beam CT (CBCT) reconstruction algorithm used for dose calculation on Varian Halcyon linear accelerators

Abstract: In this study, the performance of a new iterative reconstruction algorithm, the pre-clinical AcurosXB iCBCT algorithm, has been characterized on Varian Halcyon linear accelerators with respect to the potential of radiotherapy dose calculations on CBCT images. The study utilized various phantom setups to verify the accuracy of the pre-clinical algorithm under different scatter conditions and compared dose calculations performed on CBCT images reconstructed with the pre-clinical algorithm to those performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The proposed DE CBCT framework relies on algorithmic corrections to mitigate the impact of x-ray scatter and FPD lag and glare. While such corrections are increasingly available on advanced CBCT systems, [56][57][58][59] it is nevertheless important to understand their impact in BME imaging to inform the requirements for clinical translation. Figure 9 shows VNCa maps of Phantom-I scanned at Position 4 using 80 mm collimation; each row presents an image obtained by disabling one correction and executing the remaining processing steps and the span coefficient calibration procedure (Section 2.2.4) using the partly uncorrected input data.…”
Section: Effects Of Cbct Artifacts On Vnca Image Qualitymentioning
confidence: 99%
“…The proposed DE CBCT framework relies on algorithmic corrections to mitigate the impact of x-ray scatter and FPD lag and glare. While such corrections are increasingly available on advanced CBCT systems, [56][57][58][59] it is nevertheless important to understand their impact in BME imaging to inform the requirements for clinical translation. Figure 9 shows VNCa maps of Phantom-I scanned at Position 4 using 80 mm collimation; each row presents an image obtained by disabling one correction and executing the remaining processing steps and the span coefficient calibration procedure (Section 2.2.4) using the partly uncorrected input data.…”
Section: Effects Of Cbct Artifacts On Vnca Image Qualitymentioning
confidence: 99%
“…Moreover, since anatomical variations in patients can occur, adaptive strategies are needed to account for discrepancies between planned and delivered dose. Therefore, there has been a growing interest in utilizing CBCT imaging for plan adaptation instead of repeat computed tomography (CT) [5] , [6] , [7] , [8] . However, the lower image quality caused by photon scatter, limited field-of-view (FOV), and inconsistency in CT numbers for conventional CBCT compared to fan-beam CT can lead to lower dose calculation accuracy [2] , [9] , [10] , [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Dose calculations in photon therapy are typically based on a CT scan of the patient, with CT numbers converted to mass densities (MD) or relative electron densities (RED) by applying a conversion curve [17] , [18] . This has been adapted to CBCT in multiple studies, but the noise and scatter considerably influence the relationship between the CT numbers and corresponding MD/RED [5] , [9] , [15] , [16] , [19] , [20] , [21] , [22] . A study showed that for thoracic patients, the calibration method and accuracy were dependent on the CBCT system [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, scatter is one of the major reasons behind raw data contamination in CBCT.Improved scatter correction methods can improve CT number accuracy, and dose can be calculated more accurately by using the CBCT images directly. [28][29][30][31] This approach also simplifies the clinical workflow and reduces potential dosimetric errors associated with density overrides, deformable image registration, and synthetic CT generation. However, one potential drawback of existing methods is the accuracy of the achieved HU values through these physicsdriven approaches.…”
Section: Introductionmentioning
confidence: 99%